2023
DOI: 10.1038/s41598-023-29834-z
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for avoidance tendencies linked to anxiety about specific types of thinking

Abstract: Anxieties that are specific to a particular kind of thinking have been demonstrated for a variety of cognitive domains. One hypothesized consequence of these anxieties is reduced interest in pursuing activities and, consequentially, careers that involve the type of thinking in question in an effort to avoid engaging in that type of thinking. There is little research addressing this avoidance hypothesis, possibly because it is difficult to categorize pursuits as objectively “creative” or “spatial”. Here, we mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This is consistent with current trends in the literature which point to reliable interactions between cognitive and affective processing at both the behavioral and neural levels ( Dolcos et al 2011 ; Lerner et al 2015 ; Ochsner and Gross 2005 ; Phelps 2006 ; Storbeck and Clore 2007 ). With respect to gender differences in the spatial domain, accounting for both cognitive and affective differences may be particularly useful in identifying factors underlying disparities in avoidance of activities a person believes involve spatial thinking, such as various STEM fields ( Daker et al 2023a ). Against this backdrop, research has shown that spatial skills are important for successful engagement with STEM fields ( Gunderson et al 2012 ; Lubinski 2010 ; Uttal and Cohen 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with current trends in the literature which point to reliable interactions between cognitive and affective processing at both the behavioral and neural levels ( Dolcos et al 2011 ; Lerner et al 2015 ; Ochsner and Gross 2005 ; Phelps 2006 ; Storbeck and Clore 2007 ). With respect to gender differences in the spatial domain, accounting for both cognitive and affective differences may be particularly useful in identifying factors underlying disparities in avoidance of activities a person believes involve spatial thinking, such as various STEM fields ( Daker et al 2023a ). Against this backdrop, research has shown that spatial skills are important for successful engagement with STEM fields ( Gunderson et al 2012 ; Lubinski 2010 ; Uttal and Cohen 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple explanations have been proposed to explain these associations. Some have focused on avoidance—those who are anxious about a type of thinking tend to avoid situations that involve that type of thinking and therefore receive less practice with it 14 , 15 . Other accounts are focused on state-level impacts—feeling anxious about a type of thinking might mean higher state anxiety levels when faced with a situation that involves that type of thinking 13 15 (see below for additional detail).…”
Section: Introductionmentioning
confidence: 99%